2010
DOI: 10.1161/circresaha.110.226357
|View full text |Cite
|
Sign up to set email alerts
|

Plasma MicroRNA Profiling Reveals Loss of Endothelial MiR-126 and Other MicroRNAs in Type 2 Diabetes

Abstract: Rationale: MicroRNAs (miRNAs) have been implicated in the epigenetic regulation of key metabolic, inflammatory, and antiangiogenic pathways in type 2 diabetes (DM) and may contribute to common disease complications.Objective: In this study, we explore plasma miRNA profiles in patients with DM. Methods and Results:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

65
1,095
9
15

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,308 publications
(1,210 citation statements)
references
References 41 publications
65
1,095
9
15
Order By: Relevance
“…Furthermore, in one study miR-192 and miR-193b were reported to be deregulated in the serum of prediabetic individuals but not in that of diabetic individuals, suggesting that prediabetic, diabetic and healthy individuals have distinct profiles [26]. Finally, altered miRNA expression (miR-15a, -29b, -126, -223, -28-3p) has been observed in serum from normoglycaemic individuals who developed type 2 diabetes over a 10 year period [27]. While additional investigations are clearly needed to strengthen these findings, the results are promising, as circulating miRNAs could be early predictive biomarkers of type 2 diabetes and could help to distinguish healthy individuals from prediabetic and diabetic patients.…”
Section: Circulating Mirnas As Early Predictive Biomarkers Of Diabetesmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, in one study miR-192 and miR-193b were reported to be deregulated in the serum of prediabetic individuals but not in that of diabetic individuals, suggesting that prediabetic, diabetic and healthy individuals have distinct profiles [26]. Finally, altered miRNA expression (miR-15a, -29b, -126, -223, -28-3p) has been observed in serum from normoglycaemic individuals who developed type 2 diabetes over a 10 year period [27]. While additional investigations are clearly needed to strengthen these findings, the results are promising, as circulating miRNAs could be early predictive biomarkers of type 2 diabetes and could help to distinguish healthy individuals from prediabetic and diabetic patients.…”
Section: Circulating Mirnas As Early Predictive Biomarkers Of Diabetesmentioning
confidence: 97%
“…The observation of the deregulation of miRNA profiles in different biological fluids of diabetic patients compared with healthy controls was the first evidence supporting the idea that miRNAs could be biomarkers of the diabetic disease (Table 1). Indeed, a differential miRNA profile between type 2 diabetic patients and healthy controls was found in whole blood [20,21], serum [22][23][24][25][26], plasma [27][28][29][30][31][32][33] and plasma exosomes [34]. Studies revealed a different miRNA pattern in serum of type 1 diabetic patients compared with healthy individuals [35], as well as in plasma [36,37] and urine [36].…”
Section: Circulating Mirnas As Biomarkers Of the Diabetic Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type 2 DM has been associated with decreased endothelial cell expression of microRNA‐126 49. Stroke in type 2 DM mice significantly decreases microRNA‐126 expression in blood serum and ischemic brain tissue compared to non‐DM stroke mice 17.…”
Section: Cell‐based Therapies and Exosome Therapy For Diabetic Strokementioning
confidence: 99%
“…Dans ce type de situation, l'augmentation de certains miARN dans le sérum n'est donc qu'une conséquence indirecte de la pathologie, alors que dans d'autres cas, les miARN pourraient avoir un rôle pathogénique et participer à l'évolution de la maladie. Dans le diabète de type 2 par exemple, une modification des quantités sériques de plusieurs miARN, dont miR-126, miR-223 et miR-15a, est détectée avant même le développement de la maladie, ce qui suggère fortement l'implication directe de ces miARN dans la mise en place de la physiopathologie diabétique [31,38]. of cancer greatly increases the chances for successful treatment, the identification of accurate biomarkers is essential.…”
Section: Des Régulateurs Paracrinesunclassified